The Effect Of Return On Asset (ROA) And Debt To Equity Ratio (DER) On Stock Prices At Pt Gajah Tunggal Tbk 2013-2023 Period - Aisyah, Aisyah; Nurcahayati, Siti (Fin Sinergy: Jurnal Manajemen Keuangan, 2025)
This study aims to determine the extent of the influence of Return on Assets (ROA) and Debt to Equity Ratio (DER) partially and simultaneously on Stock Prices at PT Gajah Tunggal Tbk for the period 2013-2023. This study uses secondary data by utilizing financial reports of profitability and solvency ratios. Based on the results of this study using the t-test, it shows that this study proves that Return on Assets (ROA) partially has no significant effect on Stock Prices. This is evidenced by the calculated t value being smaller than the t-table (-0.344 < 2.306) and the sig value being greater than the significance level (0.740 > 0.050). However, Debt to Equity Ratio (DER) partially has a significant effect on Stock Prices. This can be evidenced by the calculated t value being greater than the t-table or (2.432 > 2.306) and the sig value being smaller than the significance level (0.040 < 0.050). Return On Asset (ROA) and Debt to Equity Ratio (DER) simultaneously do not affect the Stock Price at PT Gajah Tunggal Tbk for the 2013-2023 period with a calculated F value (3.653